Discovery of a Fungal Multicopper Oxidase That Catalyzes the Regioselective Coupling of a Tricyclic Naphthopyranone To Produce Atropisomers. (22nd March 2018) - Kawaguchi, Mio; Ohshiro, Taichi; Toyoda, Masayuki; Ohte, Satoshi; Inokoshi, Junji; Fujii, Isao; Tomoda, Hiroshi
Abstract: Atropisomeric dinapinones A1 and A2 (DPA1 and DPA2) were isolated from a culture of Talaromyces pinophilus FKI‐3864. Monapinone coupling enzyme (MCE), which dimerizes naphthopyranone monapinone A (MPA), was purified from a cell‐free extract of T. pinophilus FKI‐3864. MCE regioselectively dimerizes MPA at the 8, 8′‐positions to synthesize the atropisomers DPA1 and DPA2 in a ratio of approximately 1:2.5 without a cofactor. The optimal pH value and temperature for MCE were 4.0 and 50 °C, and the apparent K m and V max values for MPA were (72.7±23.2) μm and (1.21±0.170) μmol min −1  mg −1  protein. The MCE polypeptide is significantly homologous with multicopper oxidases. Heterologous expression of MCE and functional analysis confirmed that MCE catalyzes the regioselective coupling reaction of MPA to produce DPA. No fungal multicopper oxidase has previously been reported to catalyze regioselective intermolecular oxidative phenol coupling to produce naphthopyranone atropisomers.